Modelling the effect of slide table mass on machine tool energy consumption: The role of lightweighting. (January 2022) - Triebe, Matthew J.; Zhao, Fu; Sutherland, John W.
Abstract: Much of the environmental footprint of a machine tool is due to the energy consumed during its use phase. A promising strategy for reducing this energy consumption is to minimize the mass of components through changes in the design of the machine tool. This paper explores the lightweighting of the machine slides (or tables) to achieve energy savings. An energy model is developed which considers the table and workpiece mass, the cutting force, and the motor that drives the table. A case study is carried out on a three-axis vertical milling machine to explore the energy savings that can be realized via lightweighting a slide table. The model is used to compare the energy consumption of a solid table and a lightweight table. Results show a potential energy savings of up to 38% in terms of the energy required to move the table. The model is verified using experimental data already found in the literature. It was observed that the model has a lower prediction capability when the table speed and power demand are very low but as the speed and power increase the prediction capability increases significantly.